Answer:
The correct answer is option C. 3
Step-by-step explanation:
It is given an expression in variable x
(x² + 3x²)/(x + 1) ÷ (x² - 9)/(3x + 3) * (x - 3)/x
<u>To find the simplified answer</u>
x² + 3x² = x(x + 3)
x² - 9 = (x + 3)(x - 3)
The given expression can be written as,
(x² + 3x²)/(x + 1) ÷ (x² - 9)/(3x + 3) * (x - 3)/x
= x(x + 3)/(x + 1) * 3(x + 1)/(x + 1)(x - 1) * (x -3)/x
=[ x(x +3) * 3(x +1) * (x -3)]/[(x + 1) * (x + 3)(x - 3) *x]
= 3
The correct answer is option C. 3
So you are trying to multiply 6 times 3 so how can you multiply is how we know that 6×3 Is 18 so what you have to do is multiply
<span><span>1. </span>We
have the given number = 5 x 381
Let’s show how to multiply this given equation using its expanded form and
place value
=> 5 x 381
since we’re multiplying, we will start with the ones value which is 1
=> 5 x 1 = 5
Second is on the tens value
=> 5 x 80 = 400
Third is the hundreds value
=> 5 x 300 = 1 500
Now, we already have the answer to each values. Add
=> 1 500 + 400 + 5
=> 1 905</span>
<h2>>>> Answer <<<</h2>
Let's check which polynomial is divisible by ( x - 1 ) using hit , trial and error method .
A ( x ) = 3x³ + 2x² - x
The word " divisible " itself says that " it is a factor "
Using factor theorem ;
Let;
=> x - 1 = 0
=> x = 1
Substitute the value of x in p ( x )
p ( 1 ) =
3 ( 1 )³ + 2 ( 1 )² - 1
3 ( 1 ) + 2 ( 1 ) - 1
3 + 2 - 1
5 - 1
4
This implies ;
A ( x ) is not divisible by ( x - 1 )
Similarly,
B ( x ) = 5x³ - 4x² - x
B ( 1 ) =
5 ( 1 )³ - 4 ( 1 )² - 1
5 ( 1 ) - 4 ( 1 ) - 1
5 - 4 - 1
5 - 5
0
This implies ;
B ( x ) is divisible by ( x - 1 )
Similarly,
C ( x ) = 2x³ - 3x² + 2x - 1
C ( 1 ) =
2 ( 1 )³ - 3 ( 1 )² + 2 ( 1 ) - 1
2 ( 1 ) - 3 ( 1 ) + 2 - 1
2 - 3 + 2 - 1
4 - 4
0
This implies ;
C ( x ) is divisible by ( x - 1 )
Similarly,
D ( x ) = x³ + 2x² + 3x + 2
D ( 1 ) =
( 1 )³ + 2 ( 1 )² + 3 ( 1 ) + 2
1 + 2 + 3 + 2
8
This implies ;
D ( x ) is not divisible by ( x - 1 )
<h2>Therefore ; </h2>
<h3>B ( x ) & C ( x ) are divisible by ( x - 1 ) </h3>
Answer:
a + c = 95........eq1
15a + 7c = 1,025....eq2
Step-by-step explanation:
Given:
Total number of ticket sold = 95
Total amount collected = $1,025
Price of each adult ticket = $15
Price of each child ticket = $7
Computation:
Number of adult tickets sold = a
Number of child tickets sold = c
So,
Number of adult tickets sold + Number of child tickets sold = Total number of ticket sold
a + c = 95........eq1
and
15a + 7c = 1,025....eq2